A Stereomicroscopic Evaluation of Dentinal Cracks at Different Instrumentation Lengths by Using Different Rotary Files (ProTaper Universal, ProTaper Next, and HyFlex CM): An Ex Vivo Study. (29th June 2016) - Ashraf, Fauzia; Shankarappa, Pushpa; Misra, Abhinav; Sawhney, Asheesh; Sridevi, Nandamuri; Singh, Anu
Abstract : Introduction . The aim of the present study was to evaluate the dentinal cracks after root canal preparation with rotary files: Gates Glidden, ProTaper Universal, ProTaper Next, and HyFlex CM at different instrumentation lengths. Methodology . Sixty-five mandibular premolars were mounted in the acrylic tube with simulated periodontal ligaments and the apex was exposed. The root canals were instrumented with different rotary files, namely, ProTaper Universal, ProTaper Next, and HyFlex CM, to the major apical foramen (AF), short AF, and beyond AF. The root apex was stained with 1% methylene blue dye and digital images of apical surface of every tooth were taken and development of dentinal defects was determined by using stereomicroscope. Multinomial logistic regression test was performed to identify influencing factors. Results . Instrumentation with rotary files terminated 2 mm short AF and did not cause any cracks. Significantly less cracks were seen when instrumentation with rotary files terminated 1 mm short apical foramen when compared with the instrumentation terminated at or beyond apical foramen (p < 0.05 ). Conclusion . ProTaper Universal rotary files caused more dentinal cracks than ProTaper Next and HyFlex CM. Instrumentation short AF reduced the risk of dentinal defects.